1999
DOI: 10.1016/s0014-5793(99)01153-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of β‐catenin by caspases: an in vitro analysis

Abstract: Cleavage of structural proteins by caspases has been associated with the severe morphological changes occurring during the apoptotic process. One of the proteins regulating the connection of the actin filament with cadherins in a cell-cell adhesion complex is L L-catenin. During apoptosis, both an Nterminal and a small C-terminal part are removed from L Lcatenin. Removal of the N-terminal part may result in a disconnection of the actin filament from a cadherin cell-cell adhesion complex. We demonstrate that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…To address this supposition directly, we sought to identify the substrate by which caspase 3 or 8 may limit canonical signaling activity. Interestingly, ␤-catenin, the central component of the canonical Wnt pathway, is a known substrate of effector caspases (3, 6, 7) during apoptosis (62,66). Accordingly, we noted that ␤-catenin immunoblot FIG.…”
Section: Fig 3 Limited Canonical Wnt/␤-catenin Signaling In the Myomentioning
confidence: 70%
See 1 more Smart Citation
“…To address this supposition directly, we sought to identify the substrate by which caspase 3 or 8 may limit canonical signaling activity. Interestingly, ␤-catenin, the central component of the canonical Wnt pathway, is a known substrate of effector caspases (3, 6, 7) during apoptosis (62,66). Accordingly, we noted that ␤-catenin immunoblot FIG.…”
Section: Fig 3 Limited Canonical Wnt/␤-catenin Signaling In the Myomentioning
confidence: 70%
“…There is evidence suggesting that noncanonical Wnt signaling actively inhibits the canonical Wnt/␤-catenin pathway by enhancing ␤-catenin degradation through an as-yet-undefined mechanism (46,64). Interestingly, caspase proteases have been shown to target and cleave ␤-catenin, leading to a loss of canonical Wnt signal activity (62,66). Caspase activity is typically associated with apoptosis/programmed cell death, yet a growing body of evidence suggests that this protease family mediates cell fate decisions that are distinct from apoptosis/cell death (1,15).…”
mentioning
confidence: 99%
“…In atretic follicles of porcine ovaries, β-catenin expr ession is re duced concomitan tly with decreased cadherin expression. Cleaved β-catenin was detected in early atretic follicles, and the cleavage of β-catenin is probably mediated by caspases, which are essential factors of intracellular signal transduction of apoptosis [37][38][39]. Therefore, it is assumed that apoptotic signals, such as binding of Fas-ligand and tumor necrosis factors etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that b-catenin is cleaved by caspases 3, 6, and 8 (23,24). To investigate whether one or more of these caspases were responsible for the truncated b-catenin proteins, we first used STS to induce caspase activity in the wild-type cells and compared their b-catenin products with those found in the untreated, nonadherent Tsc2 2/2 cells and with STS-treated, adherent Tsc2 2/2 cells.…”
Section: Caspase 3 Activity Contributes To B-catenin Cleavagementioning
confidence: 99%